THE INFLUENCE OF THE CULTURE OF THE ORGANIZATION, ORGANIZATION COMMITMENT AND ACCOUNTABILITY TOWARDS THE PUBLIC HOSPITAL PERFORMANCE (RSUD) LUBUK BASUNG (JURNAL ECONOMICA : Research of Economic And Economic Education, 2015)
ABSTRACT This research aims to analyze: 1) the influence of organizational culture on performance of hospitals, 2) The Influence of organization commitment on hospitals performance, 3) Influence on performance accountability of hospitals. Design research is causal design. The population of the research was all the employees of the hospital as much as 131. The technique of sampling using stratified random sampling of propotional method. The number of samples is the 91 employees. Technique of data analysis performed using multiple linear regression analysis with the method of hypothesis testing using t-test and F-test.Results of the study found that: 1) organizational culture affect performance significantly to hospital. The better the organizational culture which became a role model for employees in work will surely improve the performance of hospitals. 2) The influence of Organization Commitment significantly to hospital performance. The higher the commitment to reform in the works will improve the performance of hospitals. 3) Accountability influential significantly to hospital performance. The higher the accountability would enhance the performance of hospitals. That is, the better the shape of public accountability to the performance that has been done will be able to become the driving factor in improving the performance of hospitals. Key words : organizational culture, organization commitment, accountability, performance